"(pxy-y^2)(x-py)=2py"
"({py \\over x}\\cdot x^2-y^2)(1-{py \\over x})=2{py \\over x}"
"{py \\over x}\\cdot x^2-y^2=\\dfrac{2\\dfrac{py}{x}}{1-\\dfrac{py}{x}}"
"y^2={py \\over x}\\cdot x^2-\\dfrac{2\\dfrac{py}{x}}{1-\\dfrac{py}{x}}"
Let "x^2=u, y^2=v." Then
"p=\\dfrac{dy}{dx}=\\dfrac{2x}{2y}\\cdot \\dfrac{dv}{du}=\\dfrac{\\sqrt{u}}{\\sqrt{v}}\\cdot P, P=\\dfrac{dv}{du}"
"{py \\over x}=\\dfrac{dv}{du}=P"
Substitute
We have Clairaut Equation
The general solution is given by "v=Cu+f(C), C" is an arbitrary constant.
Therefore
The general solution is
Comments
Leave a comment